(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article explores the concept of patience (sabr) in Islamic teachings, highlighting its religious, moral, and psychological dimensions. Patience is repeatedly emphasized in the Qur’an and explained in detail in the Hadiths of the Prophet Muhammad صلى الله عليه وسلم, illustrating its importance for spiritual growth, emotional stability, and social harmony. From a religious-psychological perspective, patience is not only a moral virtue but also a mechanism for managing stress, regulating emotions, and strengthening resilience. By analyzing the Hadiths, this study demonstrates that patience contributes to inner stability, moral development, and the formation of adaptive coping strategies.